Laboratory Diagnosis of Tick-Borne African Relapsing Fevers: Latest Developments - Fotso Fotso, Aurélien; Drancourt, Michel (Frontiers in Public Health, 2015)
In Africa, relapsing fevers caused by ectoparasite-borne Borrelia species are transmitted by ticks, with the exception of Borrelia recurrentis, which is a louse-borne spirochete. These tropical diseases responsible for mild to deadly spirochetemia. Cultured B. crocidurae, B. duttonii and B. hispanica circulate alongside at least six species which have not yet been cultured in vectors. Direct diagnosis is hindered by the use of non-specific laboratory tools. Indeed, microscopic observation of Borrelia spirochaeta in smears of peripheral blood taken from febrile patients lacks sensitivity and specificity. Although best visualised using dark-field microscopy, the organisms can also be detected using Wright-Giemsa or acridine orange stains.. PCR-based detection of specific sequences in total DNA extracted from a specimen can be used to discriminate different relapsing fever Borreliae. In our laboratory, we developed a multiplex real-time PCR assay for the specific detection of B. duttonii/recurrentis and B. crocidurae: Multispacer Sequence Typing accurately identified cultured relapsing fever borreliae and revealed diversity among them. Other molecular typing techniques, such as multilocus sequence analysis of tick-borne relapsing fever borreliae, showed the potential risk of human infection in Africa. Recent efforts to culture and sequence relapsing fever borreliae have provided new information for reassessment of the diversity of these bacteria. Recently, matrix-assisted laser desorption ionization time-of-flight mass spectrometry has been reported as a means of identifying cultured borreliae and of identifying both vectors and vectorised pathogens such as detecting relapsing fever borreliae directly in ticks. The lack of a rapid diagnosis test restricts the management of such diseases. We produced monoclonal antibodies against Borrelia crocidurae in order to develop cheap assays for the rapid detection of relapsing fever borreliae. In this paper, we review point-of-care diagnosis and confirmatory methods.